Prevalence and antibiotic susceptibility of Mannheimia haemolytica and Pasteurella multocida isolated from ovine respiratory infection: A study from Karnataka, southern India - Sahay, S.; Natesan, K.; Prajapati, A.; Kalleshmurthy, T.; Shome, B.R.; Rahman, Habibar; Shome, R. (Veterinary World, 2020)
Background and Aim: Respiratory infection due to Mannheimia haemolytica and Pasteurella multocida are responsible for huge economic losses in livestock sector globally and it is poorly understood in ovine population. The study aimed to investigate and characterize M. haemolytica and P. multocida from infected and healthy sheep to rule out the involvement of these bacteria in the disease. Materials and Methods: A total of 374 healthy and infected sheep samples were processed for isolation, direct detection by multiplex PCR (mPCR), and antibiotic susceptibility testing by phenotypic and genotypic methods. Results: Overall, 55 Pasteurella isolates (27 [7.2%] M. haemolytica and 28 [7.4%] P. multocida) were recovered and identified by bacteriological tests and species-specific PCR assays. Significant correlation between the detection of M. haemolytica (66.6%) with disease condition and P. multocida (19.1%) exclusively from infected sheep was recorded by mPCR. In vitro antibiotic susceptibility testing of 55 isolates revealed higher multidrug resistance in M. haemolytica (25.9%) than P. multocida (7.1%) isolates. Descending resistance towards penicillin (63.6%), oxytetracycline (23.6%), streptomycin (14.5%), and gentamicin (12.7%) and absolute sensitivity towards chloramphenicol were observed in both the pathogens. The antibiotic resistance genes such as strA (32.7%) and sul2 (32.7%) associated with streptomycin and sulfonamide resistance, respectively, were detected in the isolates. Conclusion: The study revealed the significant involvement of M. haemolytica together with P. multocida in ovine respiratory infection and is probably responsible for frequent disease outbreaks even after vaccination against hemorrhagic septicemia in sheep population of Karnataka, southern province of India.